Recent applications of bacteriophage-based electrodes: A mini-review - Marta Janczuk-Richter; Iva Marinović; Joanna Niedziółka-Jönsson; Katarzyna Szot-Karpińska (Electrochemistry Communications, 2019)
The constant search for new materials applicable in electrochemical sensors and electronic devices is encouraging scientists to turn to interdisciplinary research. Particularly interesting in this context is the combination of biology with chemistry and material sciences. Recently, bacteriophages (viruses that infect bacteria) have been increasingly used in electrochemical applications, e.g. as recognition elements in biosensors or as templates to create new electrode materials for batteries and biofuel cells. Here we present a short review of recent applications of bacteriophage-based electrodes and methods for preparing them. Keywords: Bacteriophage, Biosensor, Bioreceptor, Biotemplate, Electrode, Electrochemistry